الدعوة الإسلامية في شعر حسان بن ثابت - Saini Awang Damit (Universiti Sains Islam Malaysia, 2024)
The spread of the words of Islam are not only h t e d through the usual mediums used by dai'e and ulama but it encompasses all disciplines including poetry. The prophet Muhammad s.a.w. honors Muslim poets, and one of them being Hassan bin Thabit. It was said that the prophet Muhammad s.a.w. once told Hassan bin Thabit in his own words which means: "Act in response to the insult from the musyrikins and may Jibril join you, if all of my friends fight with weapons, you shall fight with your tongue (words)". The Prophet Muhammad s.a.w.'s stance towards poetry is encouraging, that his conduct mirrors his fondness for poetry. Not only does the prophet Muhammad s.a.w. enjoys and appreciates poetry, he even uses Muslim poets to help him oppose Islam's enemies and simultaneously spread the teachings of Islam. The Prophet appointed Hassan bin Thabit as his own personal poet to create poems to deflect the mockeries made by the musyrikin poets and at the same time enlightening them with the truth of the teaching of Islam brought by the Prophet Muhammad s.a.w. The spread of the words of 1slak through Hassan bin habit's poetry has been successful, this can be seen where he has been given support and praises for every victory that the muslimins have achieved in opposing and in combating the Prophet's and Islam's enemies by extolling Islam's greatness and the Prophet's teachings and also the unity and the strength of muslims. He also praises the Prophet and his friends whom are fighters and warriors in propagating and upholding Islam's syiar. In short, dakwah islamiyah in Hassan bin Thabit's poetry can be seen through the themes contained in his poetry, such as praises, pride, insults, lamentation, appeal etc. Truly, Hassan bin Thabit uses his poetry to defend the Prophet s.a.w. and the teachings of Islam and also the muslmns. His role and contribution in the arena of dakwah islamiyah through poetry cannot be forgotten or put aside in Islam's history. It is no wonder that he is accurately dubbed as the 'official poet', even prophet Muhammad s.a.w. dubbed him 'Abu al-Hasm' with respect to his role in defending the Prophet s.a.w. himself.